Aplikasi Digital Marketing Public Relations Miracle Mates - Dewi Andini; Maman Chatamallah (Bandung Conference Series: Public Relations, 2023)
Abstract. Digital marketing is currently one of the most popular Marketing media to support various activities. The goal is to use advertising to promote and sell products through the internet and social media. Miracle Mates is a stretch wear brand concept that was founded in 2014. To strengthen the Marketing activities of the brand, a way is needed that functions to introduce, communicate, and influence consumers to make purchases. The purpose of this study is to find out the application of digital marketing public relations Miracle Mates. The results show (1) the reason Miracle Mates use Instagram and Tiktok as media in carrying out Marketing public relations, mainly because Instagram and Tiktok are more flexible social media, and Instagram has features that support Miracle Mates in optimizing the Marketing communication process. (2) Miracle Mates has three activities to increase brand awareness. The first activity is a giveaway. Research shows that Miracle Mates on the Instagram and Tiktok apps generate positive results in Marketing efforts, giveaways are widely shared and designed to grow Miracle Mates followers on Tiktok and Instagram. In Content marketing activities, one of them is they make a match of miracle campaign on the Miracle Mates Instagram social media account in carrying out Marketing public relations, this content contains a campaign about how to support musicians and carry out activities with these musicians such as interviewing them, making events, or collaborating with the musician, in this way the followers of the musician can know the Miracle Mates brand indirectly. Furthermore, Miracle Mates does carry out paid media through Instagram Ads and also Tiktok Ads, as in the picture above, you can see one example of Instagram Ads used by Miracle Mates. (3) Obstacles that occur in the implementation of digital marketing public relations for the Miracle Mates brand, namely, occur when there is a lack of digital marketing budget funds, are not up to date with market desires, and carry out innovations and new ideas. Abstrak. Digital marketing saat ini menjadi salah satu media pemasaran yang sangat popular untuk menunjang berbagai aktivitas. Tujuannya menggunakan periklanan untuk mempromosikan dan menjual produk melalui internet dan media sosial. Miracle Mates merupakan brand berkonsep streat wear brand yang berdiri di tahun 2014. Untuk memperkuat kegiatan Marketing dari brand tersebut, dibutuhkan cara yang berfungsi untuk memperkenalkan, mengkomunikasikan, dan mempengaruhi konsumen untuk melakukan pembelian. Tujuan dalam penelitian ini yaitu untuk mengetahui aplikasi digital marketing public relations Miracle Mates. Hasil penelitian menunjukkan (1) Alasan Miracle Mates menggunakan Instagram dan Tiktok sebagai media dalam melaksanakan marketing public relations, utamanya yaitu karena Instagram dan Tiktok menjadi media sosial yang lebih fleksibel, serta Instagram memiliki fitur-fitur yang menunjang Miracle Mates dalam mengoptimalkan proses komunikasi pemasaran; (2) Miracle Mates memiliki tiga aktivitas untuk meningkatkan brand awareness. Kegiatan pertama adalah giveaway. Penelitian menunjukkan bahwa Miracle Mates pada aplikasi Instagram dan Tiktok menimbulkan hasil positif dalam upaya pemasaran, giveaway dibagikan secara luas dan dirancang untuk menumbuhkan pengikut Miracle Mates di Tiktok dan Instagram. Dalam kegiatan content marketing, salah satunya mereka membuat campaign match of miracle pada akun media sosial Miracle Mates Instagram dalam melaksanakan marketing public relations, konten ini berisi campaign tentang bagaimana men support musisi–musisi dan melakukan kegiatan dengan musisi tersebut seperti mewawancarainya, membuat event, atau kolaborasi dengan musisi tersebut, dengan cara tersebut maka pengikut dari musisi itu dapat mengetahui brand Miracle Mates secara tidak langsung. Selanjutnya bahwa Miracle Mates memang melaksanakan paid media melalui Instagram Ads dan juga Tiktok Ads; (3) Kendala yang terjadi dalam pelaksanaan digital marketing public relations brand Miracle Mates yaitu terjadi ketika kurangnya anggaran dana digital marketing, tidak up to date dengan keinginan pasar, dan melakukan inovasi dan ide-ide baru.